2018
DOI: 10.3390/bioengineering5010011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heterologous tRNA Modifications on the Production of Proteins Containing Noncanonical Amino Acids

Abstract: Synthesis of proteins with noncanonical amino acids (ncAAs) enables the creation of protein-based biomaterials with diverse new chemical properties that may be attractive for material science. Current methods for large-scale production of ncAA-containing proteins, frequently carried out in Escherichia coli, involve the use of orthogonal aminoacyl-tRNA synthetases (o-aaRSs) and tRNAs (o-tRNAs). Although o-tRNAs are designed to be orthogonal to endogenous aaRSs, their orthogonality to the components of the E. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…For instance, the NAAs with bulky or extremely charged chemical group are unable to effectively cross cellular membrane, thus, the successful approach to evolve orthogonal pairs and site-specifically incorporate such a NAAs would be either propeptide strategy utilizing NAAs in dipeptide form [114] or modification of the host organism transport system, such as engineering of periplasmic binding protein, for optimized uptake of the desired NAA into the cell [115]. Very recently the significance of heterologous cellular background, particularly the enzymes modifying the orthogonal tRNA, for NAA-containing protein synthesis was demonstrated [116]. Another important issue to consider is the permissivity of the mutation site, i.e., sequence flexibility representing an ability to tolerate a large number of mutations at a selected locus without significant loss in protein activity [117].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the NAAs with bulky or extremely charged chemical group are unable to effectively cross cellular membrane, thus, the successful approach to evolve orthogonal pairs and site-specifically incorporate such a NAAs would be either propeptide strategy utilizing NAAs in dipeptide form [114] or modification of the host organism transport system, such as engineering of periplasmic binding protein, for optimized uptake of the desired NAA into the cell [115]. Very recently the significance of heterologous cellular background, particularly the enzymes modifying the orthogonal tRNA, for NAA-containing protein synthesis was demonstrated [116]. Another important issue to consider is the permissivity of the mutation site, i.e., sequence flexibility representing an ability to tolerate a large number of mutations at a selected locus without significant loss in protein activity [117].…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why ∆ miaA produces more antimycins and novel compounds as compared to parental SAM2 strain. At present we are not aware of any reports, where deficiency in modification of natural tRNA would lead to improved expression of a certain trait (however, precedents are known for heterologous tRNA that mediate incorporation of nonstandard amino acids in E. coli ; Crnković et al , ). As in the related species S. albus S4, antimycin and candicidin gene clusters are grouped together in J1074 genome (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A genetic approach to addressing this issue involves monitoring ncAA incorporation and reporter protein yields across E. coli or yeast strain collections containing deletions and/or the overexpression cassettes of metabolic genes. Recently it was shown that the yield and specificity of O- phosphoserine incorporation is significantly improved by the deletion of cysteine desulfurase and the overexpression of E. coli dimethylallyltransferase (MiaA) and pseudouridine synthase (TruB) [ 65 ]. Furthermore, a yeast study involving the removal of modifications by single gene deletions from U34, U35, A37, U47 and C48 in the anticodon stem-loop impairs nonsense suppression, with the strongest effect observed for U34 and A37.…”
Section: Aspects Of Heterologous Trna Expressionmentioning
confidence: 99%